PENGEMBANGAN MEDIA PEMBELAJARAN BIG BUSY BOOK UNTUK MENINGKATKAN PERKEMBANGAN BAHASA ANAK USIA 4-5 TAHUN DI TK AS SYAFI`IYAH BICORONG PAKONG PAMEKASAN - Anisa Puspitasari; Musayyadah Musayyadah; Novianti Nur Imani (Journal of Education Partner, 2023)
Based on the results of initial observations carried out by researchers at the As Syafi`iyah Bicorong Pakong Pamekasan Kindergarten, a problem was found, namely the low level of children's language development, due to the lack of use of learning media in the process of developing the language skills of children aged 4-5 years, so that learning is still centered on teachers and children. more passive, the media used is limited to magazines, student worksheets and blackboards. This research and development aims to 1) produce appropriate and valid learning media to improve the language development of children aged 4-5 years 2) produce learning media that suits the needs and language development of children aged 4-5 years 3) produce effective learning media, efficient and interesting for the language development of children aged 4-5 years/group A at Kindergarten As Syafiiyah Bicorong Pakong Pamekasan. The research method used was Research and Development with the Borg and Gall research model up to step 7. The subjects of this research were As Syafi`iyah Bicorong Pakong Kindergarten students aged 4-5 years. The small group formative test subjects were 6 children. And the formative test subjects were a large group of 14 children. Research data was obtained from the results of observation, interviews, questionnaires and documentation methods. The overall results from expert validation averaged 95%. The small group formative test got a percentage of 95.82%, the large group formative test got a percentage of 97.34%, these results refer to aspects of attractiveness, efficiency and effectiveness which are in accordance with the level of language development achievement of children aged 4-5 years. Conclusion of research and development of Big Busy Book learning media. To achieve the level of language development of children aged 4-5 years based on expert validation and small group and large group formative tests which are at the criteria (86%-100%) then the Big Busy Book learning media can improve the language development of children aged 4-5 years. stated to be very valid and can be used. From the results of the development, it is recommended that this learning media can be used and developed further because this research is only focused on the language development of children aged 4-5 years with the theme of animals. It is hoped that later this research can be developed again with a more complete theme and can improve all aspects. development in early childhood.